THE RELATIONSHIP OF HALAL CERTIFICATION, ONLINE REVIEW TOWARD RE-PURCHASE INTENTION AND RELIGION BELIEF AS AN INTERVENING VARIABLE ON YOUNG MUSLIM CONSUMER - Hanny Humairatunnisaa (Universitas Mercu Buana, 2022)
Indonesia is the largest Muslim population in the world, and having a halal certification is mandatory in Indonesia since 17 October 2019 based on Law Number 33 of 2014 Concerning halal product guarantee. The purpose of this paper is to analyze the relationship of halal certification and online reviews that can affect chatime young Muslim consumers to repurchase the product. The paper uses causal research that aims to know about The Relationship of Halal Certification, Online Review toward Re-purchase Intention, and Religion Belief as Intervening Variable. Evidence supports by collecting the data with a questionnaire and take Indonesian consumers (Chatime consumer) as a population and the number population is unknown. The sampling method that uses for this paper is the purposive sampling technique and using Lemeshow calculation to determine the number of samples and the result need 100 samples or respondents in order to obtain more representative data. The PLS method analyzes and describe the data. The result of the study indicates that Halal Certification has a positive and significant effect on Re-purchase Intention, Religion Belief and Online Review has a positive and significant effect on Re-purchase Intention, Online Review has positive and not significant result to Religion Belief, Religion Belief has positive and not significant result to Re-purchase Intention.Keywords: Halal Certification, Online Review, Re-purchase Intention, Religion Belief,